Occurrence of organochlorine pesticides (OCPs) and their enantiomeric signatures, and concentrations of polybrominated diphenyl ethers (PBDEs) in the Adelie penguin food web, Antarctica - CORSOLINI, S.; COVACI, A.; ADEMOLLO, N.; FOCARDI, S.; SCHEPENS, P. (Environmental Pollution, 2006)
Concentrations and enantiomeric signatures of organochlorine pesticides were determined in Antarctic krill, emerald rockcod and Adélie penguin from the Ross Sea, Antarctica. HCB and DDTs were prevalent contaminants in penguin eggs. The highest concentrations of ΣHCHs (1.35 ± 0.72 ng/g) were found in the rockcod muscle, where γ-HCH (1.23 ± 0.67 ng/g) was the principal isomer. The ratio γ-HCH/α-HCH was evaluated. Enantioselective gas chromatography was used for the evaluation of enantiomeric fractions (EFs) for α-HCH and oxychlordane. An increase of 14% in the (+)α-HCH enantiomer was found from krill through penguin, suggesting the enantioselective biotrasformation increased proportionately with trophic level. Polybrominated diphenyl ethers (PBDEs) were measured and their concentrations were 5.6 ± 1.12, 5.81 ± 2.32, 4.57 ± 0.17 and 3.06 ± 3.27 ng/g lipids in krill, rockcod muscle, rockcod homogenate and penguin eggs, respectively. The detection of BDE28, BDE47, BDE99 and BDE100 in Antarctic organisms confirmed their global transport and distribution; the detection of lower brominated congeners suggested a potential long-range transport.